A soil column apparatus for laboratory infiltration study - Yang, Hong (2011)
In this paper, the details of a large-scale soil column apparatus, the procedures for constructing the soil column, and the performance of the apparatus are presented. This paper aims to describe the apparatus that is capable of performing comprehensive infiltration study rather than to describe one particular infiltration study or phenomenon. By using the apparatus, all the variables (pore-water pressures, water contents, inflow rate, and outflow rate) in an infiltration process can be measured instantaneously and automatically, and all the boundary conditions can be controlled. The major instruments for the soil column apparatus consist of a tensiometer-transducer system, data acquisition system, time-domain reflectometry, and electronic weighing balance. By using these instruments, relationships of the volumetric water content versus matric suction of the soil and the infiltration rate versus time at any point of time during an infiltration test can be obtained. The test results also show that the setup functioned properly and suggest that infiltration behavior of any soil configuration (single, two-layered, or multilayered soil) can be studied using this apparatus for different infiltration rates.